Role of natural resources utilization efficiency in achieving green economic recovery: Evidence from BRICS countries. (January 2023) - Zhao, Linhai; Rasoulinezhad, Ehsan
Abstract: The main goal of this article is to evaluate and analyze the effect of natural resources utilization efficiency on green economic growth in 5 emerging economies (Brazil, Russia, India, China, and South Africa) in the BRICS group. The panel data approach is employed to estimate coefficients by calculating the resource activity coefficient and gathering annual data for 2000–2020. The major results confirm that natural resource utilization efficiency accelerates the green economic growth of BRICS countries. Moreover, the presence of an uni-directional causal linkage from resource utilization efficiency to green economic growth is concluded, meaning that in the short-term, natural resource utilization efficiency can cause green economic growth in BRICS economies. As practical policies, promoting green FDI to increase green technologies transfer, green financing to promote technological innovation, and implementing the principle of 3Rs (Reduce, reuse, recycle) are recommended. Highlights: Natural resource utilization efficiency accelerates green economic growth of BRICS countries. There is an uni-directional causal linkage running from resource utilization efficiency to green economic growth. There exists the Halo Pollution Hypothesis (HPH) in BRICS.